Wo ist Gott in der Pandemie?: Theologische Überlegungen aus Praxis und Reflexion kirchenleitenden Handelns - Bedford-Strohm, Heinrich (Evangelische Theologie, 2021)
The pandemic has confronted the churches with various difficult questions both practical and theological. Is there a responsible way of celebrating worship in the churches without risking people’s health? Numerous creative new digital formats were developed in the parishes to offer alternatives. How does God work in the pandemic? Is there any causal connection between God and the virus? The responses to this question are not only of philosophical importance, but have fundamental consequences on how we pray and how we identify God's presence in our lives. Some responses affirm God's role in the origin of the virus, e.g. by identifying the work of the deus absconditus in it, others emphasize the mysteriousness of God's action, others see God's action in God's spirit of creative energy to overcome suffering in human and non-human nature. The latter approach is developed by an understanding of God based on God's revelation in Jesus Christ and an eschatological interpretation of its visibility beyond current experiences of destruction and despair.